PENGARUH PENDIDIKAN AQIDAH AKHLAK TERHADAP PERILAKU SISWA KELAS V MADRASAH IBTIDAYAH NEGERI 1 KEPAHIANG PROVINSI BENGKULU - Adisel; Saleli Monika (STKIP Subang, 2024)
This research aims to analyze the influence of Aqidah Akhlak education on the behavior of class V students at MIN 1 Kepahiang. Aqidah Akhlak education is an important component in the Islamic religious education curriculum which aims to shape students' character and morals. The research method used is quantitative with a survey approach. Data was collected through questionnaires distributed to 25 class V MIN 1 Kepahiang students, as well as observations and interviews with teachers and students. The research results show that Aqidah Akhlak education has a positive and significant influence on student behavior. Students who receive intensive Aqidah Akhlak education tend to show better behavior, such as honesty, discipline, responsibility and respect for others. This effect can be seen from the increase in positive behavior scores in students after they received Aqidah Akhlak education. After the author carried out research, he obtained an r of 0.396 and a t count of 2.566, which also resulted in a determination of. This means that the influence of Aqidah Akhlak education on student behavior is accepted, meaning that there is an influence obtained and resulting from learning influencing students' morals. The conclusion of this research is that Aqidah Akhlak education plays an important role in shaping the positive behavior of class V students. It is recommended that schools further intensify the Aqidah education program. Morals and involving parents in this educational process to achieve more optimal results. After the author carried out research, he obtained an r of 0.396 and a t count of 2.566, which also resulted in a determination of . This means that the influence of moral aqidah education on student behavior is accepted, meaning that there is an influence obtained and the results of learning influence student morals.